2005
DOI: 10.1164/rccm.200408-1088oc
|View full text |Cite
|
Sign up to set email alerts
|

Fluticasone Improves Pulmonary Function in Children under 2 Years Old with Risk Factors for Asthma

Abstract: This study assessed the effects of treatment with fluticasone in children younger than 2 years old with recurrent wheezing and risk factors of developing asthma. This double-blind placebo-controlled study randomized children to receive fluticasone (125 mug; n = 14) or placebo (n = 12) twice daily for 6 months. Pulmonary function was assessed at the beginning and end, and parents filled out a daily diary recording respiratory symptoms, need for rescue medication, and emergency care. The SD score of maximum flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
2
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 32 publications
4
30
2
4
Order By: Relevance
“…Atopic markers, such as a history of atopic dermatitis or allergic rhinitis, did not improve the chance of responding to ICSs [111]. However, preschool children with wheeze, selected based on the asthma predictive index for the prediction of persistent wheeze (including atopic dermatitis, allergic rhinitis and eosinophilia), respond to ICSs as a group [40,41].…”
Section: Inhaled Corticosteroidsmentioning
confidence: 98%
See 1 more Smart Citation
“…Atopic markers, such as a history of atopic dermatitis or allergic rhinitis, did not improve the chance of responding to ICSs [111]. However, preschool children with wheeze, selected based on the asthma predictive index for the prediction of persistent wheeze (including atopic dermatitis, allergic rhinitis and eosinophilia), respond to ICSs as a group [40,41].…”
Section: Inhaled Corticosteroidsmentioning
confidence: 98%
“…In an attempt to predict which preschool wheezers continue to wheeze beyond the age of 6 yrs, these history data have been combined with characteristics such as blood eosinophilia into an asthma predictive index [39]. Although groups of children with a positive asthma predictive index respond to inhaled corticosteroid (ICS) therapy [40,41], the predictive value of this index for the disappearance or persistence of wheeze over time in individual patients is of only modest clinical value [39].…”
Section: Multiple-trigger Wheezementioning
confidence: 99%
“…2 In addition, several placebocontrolled trials have indicated that inhaled corticosteroids delivered by VHC/mask are effective for treating persistent asthma in young children. [3][4][5][6][7] Recommendations for optional drug delivery by a pMDI alone include deep inhalation from end-tidal volume followed by a 10-second breath hold. 1 In contrast, young children require a VHC/mask to deliver drug from a pMDI and generally breathe only at tidal volume, resulting in less volume inhaled per breath.…”
mentioning
confidence: 99%
“…Teper et al 21 measured growth velocity over a 6-month period in children receiving FP 125 or placebo; there was no statistically significant difference between the groups at the end of the study period. Bisgaard et al 23 compared intermittent use of budesonide 400mcg or placebo in the first three years of life, and there was no difference between the two groups in growth measured by stadiometry or in bone mineral density measurements.…”
Section: Low Rates Of Ics Side Effects In Young Childrenmentioning
confidence: 99%
“…There was a statistically significant benefit for ICS in terms of lung function, the need for rescue medication, and the percentage of symptom-free days. 21 Although not all studies in very young children have shown ICS to be clinically and significantly beneficial, the UK study by Chavasse and colleagues, published in 2001, showed that persistent wheezing in infants with an atopic tendency responded to inhaled FP. 22 …”
Section: Lung Function Studies In Very Young Childrenmentioning
confidence: 99%